2022
DOI: 10.3390/cells11132091
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Phenotypes in Aging and Neurodegenerative Diseases

Abstract: Neuroinflammation is a hallmark of many neurodegenerative diseases (NDs) and plays a fundamental role in mediating the onset and progression of disease. Microglia, which function as first-line immune guardians of the central nervous system (CNS), are the central drivers of neuroinflammation. Numerous human postmortem studies and in vivo imaging analyses have shown chronically activated microglia in patients with various acute and chronic neuropathological diseases. While microglial activation is a common featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 432 publications
0
72
1
Order By: Relevance
“…However, recent research has shown that these traditional phenotypic classifications of microglia are not all inclusive, and alternative and intermediate forms may exist [31,34]. Studies investigating microglia activation after CNS injury or illness have noted that the M1/M2 microglial classification is simplistic, as multipurpose and alternative forms have been identified after injury [37,38]. For example, the anti-inflammatory and regenerative M2 form has been further subdivided into M2a, M2b, M2c [33,39,40] and M2d subtypes [38,41].…”
Section: Immunological Moderators Of Cns Injury and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research has shown that these traditional phenotypic classifications of microglia are not all inclusive, and alternative and intermediate forms may exist [31,34]. Studies investigating microglia activation after CNS injury or illness have noted that the M1/M2 microglial classification is simplistic, as multipurpose and alternative forms have been identified after injury [37,38]. For example, the anti-inflammatory and regenerative M2 form has been further subdivided into M2a, M2b, M2c [33,39,40] and M2d subtypes [38,41].…”
Section: Immunological Moderators Of Cns Injury and Diseasementioning
confidence: 99%
“…Studies investigating microglia activation after CNS injury or illness have noted that the M1/M2 microglial classification is simplistic, as multipurpose and alternative forms have been identified after injury [37,38]. For example, the anti-inflammatory and regenerative M2 form has been further subdivided into M2a, M2b, M2c [33,39,40] and M2d subtypes [38,41]. The M2a form is activated by IL-4 and IL-13 and plays a role in anti-parasitic responses in that it increases scavenger receptors and induces phagocytosis, IL-10 secretion, and tissue growth and repair [33,39,41].…”
Section: Immunological Moderators Of Cns Injury and Diseasementioning
confidence: 99%
“…Several immunogenic types with inflammatory and interferon-responsive profiles persist throughout the lifespan and increase with time (Hammond et al, 2019 ). Senescent microglia, referred to as “primed microglia,” are hypersensitive to neurotoxic and inflammatory insults, and they express high levels of pro-inflammatory mediators and reactive species, while showing deficits in phagocytosis and motility (Buga et al, 2013 ; Rawji et al, 2016 ; Wendimu and Hooks, 2022 ). Age exacerbates white matter damage, deteriorates functional outcomes and increases the severity of secondary neurodegeneration after stroke (Suenaga et al, 2015 ; Kluge et al, 2018 ).…”
Section: Activation Of Microglia Following Ischemic Strokementioning
confidence: 99%
“…An imbalance of these microglial functions may trigger the onset or exacerbation of neurodegeneration, a severe and debilitating neuroinflammatory disease that may occur as a result of specific and persistent stimuli, with progressive degeneration and death of neurons. All of this is because of microglia cells, which could also damage and kill neurons, depending on the type of inflammatory response, resulting in psychomotor damage, which characterizes the phenotype of neurodegenerative diseases [ 79 ]. Noteworthy, MKD syndromes are characterized, among the other clinical features, by recurrent episodes of fever, one of the clinical signs that unites autoinflammatory diseases with other inflammatory symptoms and neurological involvement especially in the most severe forms (mental and psychomotor retardation, progressive cerebellar ataxia, visual impairment, epilepsy) [ 6 ].…”
Section: Neuroinflammation Oxidative Stress and Fever As A Consequenc...mentioning
confidence: 99%